2019
DOI: 10.4034/pboci.2019.191.96
|View full text |Cite
|
Sign up to set email alerts
|

Structural Assessment of Chemical Constituent of Sidaguri (Sida rhombifolia Linn) and Its Ability to Inhibit Cyclooxygenase

Abstract: Objective: To elicit the structure of isolated compounds from roots of sidaguri (Sida rhombifolia Linn). Material and Methods: Several organic standard protocols were involved, including extraction, fractionation, and phytochemical testing. Further spectroscopy methods, FTIR and 1HNMR, were used to determine the predicted structure of molecules, while their ability to inhibit cyclooxygenase (COX 1 and 2) were tested using in vitro method. Results: Overall assessments showed that the structure of the sidaguri i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…14 In dental practice, clove oil, gambir, jatropha, sidaguri and bee venom have been usually used to relieve dental pain by applying them directly to the affected tooth. [4][5][6][7] A preliminary in vitro study in an animal model with periapical lesion showed that the root of sidaguri was able to decrease C-reactive protein level (CRP), one of many molecules that take part in the acute inflammatory process. 8 Another study showed that root of sidaguri was a non-selective COX inhibitor, an enzyme involved in the synthesis of prostaglandin E2.…”
Section: Discussionmentioning
confidence: 99%
“…14 In dental practice, clove oil, gambir, jatropha, sidaguri and bee venom have been usually used to relieve dental pain by applying them directly to the affected tooth. [4][5][6][7] A preliminary in vitro study in an animal model with periapical lesion showed that the root of sidaguri was able to decrease C-reactive protein level (CRP), one of many molecules that take part in the acute inflammatory process. 8 Another study showed that root of sidaguri was a non-selective COX inhibitor, an enzyme involved in the synthesis of prostaglandin E2.…”
Section: Discussionmentioning
confidence: 99%
“…The active compound Sidaguri has an anti-inflammatory effect by non-selectively inhibiting COX. (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the Usada Wariga Dalem text it is also mentioned that the sidaruri plant can be used as a fever reducer. If you look at the results of research on these plants, sidaguri contains active compounds that have an anti-inflammatory effect by non-selectively inhibiting COX (16).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the phytoconstituents reported in fractions were summarized in Table 5 as per earlier reports. [22][23][24][25] Journal of Young Pharmacists, Vol 13 Issue 4, Oct-Dec, 2021…”
Section: In Vitro Ache Inhibitionmentioning
confidence: 99%